Emerin self‐assembly mechanism: role of the LEM domain. (9th January 2017) - Samson, Camille; Celli, Florian; Hendriks, Kitty; Zinke, Maximilian; Essawy, Nada; Herrada, Isaline; Arteni, Ana‐Andreea; Theillet, François‐Xavier; Alpha‐Bazin, Béatrice; Armengaud, Jean; Coirault, Catherine; Lange, Adam; et al.
Abstract : At the nuclear envelope, the inner nuclear membrane protein emerin contributes to the interface between the nucleoskeleton and the chromatin. Emerin is an essential actor of the nuclear response to a mechanical signal. Genetic defects in emerin cause Emery–Dreifuss muscular dystrophy. It was proposed that emerin oligomerization regulates nucleoskeleton binding, and impaired oligomerization contributes to the loss of function of emerin disease‐causing mutants. We here report the first structural characterization of emerin oligomers. We identified an N‐terminal emerin region from amino acid 1 to amino acid 132 that is necessary and sufficient for formation of long curvilinear filaments. In emerin monomer, this region contains a globular LEM domain and a fragment that is intrinsically disordered. Solid‐state nuclear magnetic resonance analysis identifies the LEM β‐fragment as part of the oligomeric structural core. However, the LEM domain alone does not self‐assemble into filaments. Additional residues forming a β‐structure are observed within the filaments that could correspond to the unstructured region in emerin monomer. We show that the delK37 mutation causing muscular dystrophy triggers LEM domain unfolding and increases emerin self‐assembly rate. Similarly, inserting a disulfide bridge that stabilizes the LEM folded state impairs emerin N‐terminal region self‐assembly, whereas reducing this disulfide bridge triggers self‐assembly. We conclude that the LEM domain, responsible for binding to the chromatin protein BAF, undergoes a conformational change during self‐assembly of emerin N‐terminal region. The consequences of these structural rearrangement and self‐assembly events on emerin binding properties are discussed. Abstract : Nuclear envelope structure is regulated by protein oligomerization and post‐translational modification. Inner nuclear envelope LEM domain proteins such as emerin are mutated in several human genetic diseases. We show that emerin mutation delK37 causes LEM unfolding and favors emerin oligomerization; we identify structural determinants of the corresponding oligomers. We propose an oligomerization‐dependent mechanism for the regulation of nucleoskeleton and chromatin recognition.